A real-world pharmacovigilance study of adverse drug reactions associated with lecanemab and aducanumab based on WHO-VigiAccess and FAERS databases - Hu, Haoxiang; Zhao, Yunhan; Mao, Jiesheng; He, Jianghai; Zhang, Yihan; Ye, Hongyu; Yang, Xiaokai (Frontiers in Pharmacology, 2025)
BackgroundLecanemab and Aducanumab are two novel anti-amyloid beta (Aβ) therapies for Alzheimer’s disease (AD) that have shown promise in slowing cognitive decline. However, their safety profiles remain unclear due to limited real-world evidence. This study aims to analyze and compare adverse drug reactions (ADRs) of these drugs using data from the WHO-VigiAccess and FAERS databases.MethodsA retrospective analysis was conducted using ADR data from the VigiAccess and FAERS databases, focusing on System Organ Class (SOC) and Preferred Term (PT) classifications. Descriptive statistics and reporting odds ratio (ROR) analysis were employed to evaluate and compare ADR profiles.ResultsLecanemab and Aducanumab exhibited distinct ADRs. Results from both the VigiAccess and FAERS databases indicated that the most SOC associated with both drugs was nervous system disorders (34.7% in VigiAccess, 36.8% in FAERS). Further multivariable logistic regression analysis revealed that Aducanumab was associated with a higher risk of nervous system disorders (OR = 4.72, 95% CI: 3.53–6.39, P < 0.001). Among the reported AEs, headache was the most frequently reported for Lecanemab (9.4% in VigiAccess, 8.96% in FAERS), while Aducanumab was primarily associated with amyloid-related imaging abnormalities (ARIA) (19.1% in VigiAccess, 23.58% in FAERS). In the blood and lymphatic systems, Anemia was observed in both drugs. However, thrombocyto-penia was more prevalent in Lecanemab, while platelet dysfunction and myelosuppression were more frequently observed in Aducanumab. Additionally, hospitalization and mortality rates were higher for Aducanumab compared to Lecanemab.ConclusionThis study compared the ADRs of Lecanemab and Aducanumab, revealing that ARIA was the most common AE for both drugs. However, Lecanemab showed a lower risk of ARIA, cerebral hemorrhage, and severe events. These findings emphasize the need for further clinical research to clarify the long-term safety and efficacy of both drugs.